Recurrence of primary disease following lung transplantation. Issue 2 (30th May 2022) - Rama Esendagli, Dorina; Ntiamoah, Prince; Kupeli, Elif; Bhardwaj, Abhishek; Ghosh, Subha; Mukhopadhyay, Sanjay; Mehta, Atul C.
Lung transplant has become definitive treatment for patients with several end-stage lung diseases. Since the first attempted lung transplantation in 1963, survival has significantly improved due to advancement in immunosuppression, organ procurement, ex vivo lung perfusion, surgical techniques, prevention of chronic lung allograft dysfunction and bridging to transplant using extracorporeal membrane oxygenation. Despite a steady increase in number of lung transplantations each year, there is still a huge gap between demand and supply of organs available, and work continues to select recipients with potential for best outcomes. According to review of the literature, there are some rare primary diseases that may recur following transplantation. As the number of lung transplants increase, we continue to identify disease processes at highest risk for recurrence, thus shaping our future approaches. While the aim of lung transplantation is improving survival and quality of life, choosing the best recipients is crucial due to a shortage of donated organs. Here we discuss the common disease processes that recur and highlight its impact on overall outcome following lung transplantation. This article reviews the underlying conditions leading to lung transplant with potential for recurrence and the impact of such recurrences on the overall outcome following transplant https://bit.ly/3v3gSvJ